The Urgency of Artificial Intelligence in Learning Islamic Religious Education - Mela, Lita (Proceeding International Conference on Religion, Science and Education, 2024)
Artificial Intelligence has advantages and disadvantages in education. In Islamic religious education, there is still a lot of debate about the use of Artificial Intelligence. This makes teachers afraid to make breakthroughs because they think that breakthroughs such as Artificial Intelligence can damage students' character and so on, even though if Artificial Intelligence is used as well as possible it will have a positive impact on Islamic religious education. To study the urgency of using artificial intelligence in Islamic religious education, researchers used a qualitative literature study method sourced from national and international scientific books and articles that discuss artificial intelligence and Islamic religious education as well as the Al-Qur'an and hadith which are its basis. The research results show that it is very crucial in learning Islamic religious education to use Artificial Intelligence as a tool in the learning process which can create interesting learning products and as a means of developing students' ideas to always develop and innovate without violating the Al-Qur'an and Hadith, this is useful not only to achieve learning goals but also for the advancement of Islamic religious education itself.